Food justice youth development: using Photovoice to study urban school food systems*. Issue 7 (3rd July 2017) - Harper, Krista; Sands, Catherine; Angarita Horowitz, Diego; Totman, Molly; Maitín, Monica; Rosado, Jonell Sostre; Colon, Jazmin; Alger, Nick
ABSTRACT: How do youth learn through participation in efforts to study and change the school food system? Through our participatory youth action research (YPAR) project, we move beyond the "youth as consumer" frame to a food justice youth development (FJYD) approach. We track how a group of youth learned about food and the public policy process through their efforts to transform their own school food systems by conducting a participatory evaluation of farm-to-school efforts in collaboration with university and community partners. We used the Photovoice research method, placing cameras in the hands of young people so that they themselves could document and discuss their concerns and perspectives. The research was designed to gain insight about youths' knowledge of food, health, and community food systems. Drawing upon the youth group's insights, we build a framework for building critical consciousness through FJYD.